A física moderna e contemporânea no ensino médio : qual sua presença em sala de aula? - Sanches, Mônica Bordim (2006)
The issue discussed in this essay deals with the teaching of Physics, with special regard to Modern and Contemporary Physics (MCF) at the upper high school. Its actuality in the classroom has been verified in the context of teachers, students and textbooks which are extremely important for the understanding of the complexity of the teaching-learning process. In fact, the processes that involve the construction processes of knowledge, which lead towards the curricular updating of Physics in the upper high school, are revealed. Twelve textbooks used by teachers of the government public schools have been analyzed so that the manner MCF is being approached in the books may be debated. Two questionnaires, for students and teachers respectively, on the different topics that make up this complex theme have also been applied so that the students' and teachers' ideas on the subject may be known. Data have been analyzed by Content Analysis techniques. Results show that textbooks reveal that there has been an MCF insertion within the upper high school even though their approach is highly inadequate. Further, although they are unprepared to deal with MCF in the classroom and although they have listed a number of issues in the context of curricular updating, teachers agree that the Physics curriculum should be thoroughly revised and new topics inserted. The students' questionnaires confirmed once more the hypothesis that teaching fails to stimulate the curiosity and the cognitive capacity of the student. In fact, it is the cause of their distancing from the contents dealt with in Physics. They also present ambiguous concepts on MCF themes. It may be concluded that the manner the teaching of Physics is dealt with, or rather, Physics textbooks with an excessive insistence on formulas and mathematics coupled to an exclusion of phenomena and concepts, reduced hour load and deficient teachers' training, its role will continue to be low key in students' training. In fact, a wider cognition of the discipline and a world view which includes daily issues will remain utterly excluded.